Toward Sustainable Hydroxymethylfurfural Production Using Seaweeds. Issue 5 (May 2020) - Heo, Jae Bok; Lee, Yong-Suk; Chung, Chung-Han
Abstract : Chemical manufacturing involves carbon sources releasing CO2 into the atmosphere. By contrast, seaweeds are carbon sinks that can absorb released CO2 and therefore have great potential for use as feedstocks in sustainable chemical manufacturing. In particular, seaweeds could contribute to mitigating vast amounts of global CO2 emissions. Accordingly, seaweeds could be an excellent candidate biomaterial for sustainable production of hydroxymethylfurfural (HMF), called a 'sleeping giant' platform chemical due to its wide versatility in chemical manufacturing. HMF is produced through sugar dehydration mechanisms, and seaweed storage glucans comprised of glucose can be appropriate feeding substrates for its production. This opinion article introduces a new opportunity for sustainable production of HMF using storage glucan-rich seaweeds. Highlights: Raw seaweeds rich in storage glucans could be optimal biomaterials for sustainable production of HMF. Seaweed-based bioprocesses could contribute to reducing CO2 emissions released from the chemical industry. A biostrategy for enhancing seaweed growth could help to reduce HMF production costs. A biostrategy for augmenting storage glucans of seaweeds could apply to other algal species. A conversion technology of algal storage glucans could be applicable for the production of HMF from other similar bio-based polymers.